2019
DOI: 10.1155/2019/7836527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Fimasartan versus Valsartan on Blood Pressure Variability in Acute Ischemic Stroke: A Double-Blind Randomized Trial

Abstract: Higher blood pressure variability (BPV) is associated with poor functional outcome and mortality in acute stroke. This randomized controlled trial was conducted to compare the effect on BPV between fimasartan and valsartan (Boryung Pharmaceutical Co., Ltd., Seoul, Republic of Korea) in patients with acute ischemic stroke. Eighty patients were randomly assigned to receive either valsartan or fimasartan after 7 days of acute ischemic stroke onset, for duration of 8 weeks. Of them, 62 patients completed the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…One small, single-center, double-blind, randomised clinical trial, that was conducted in Korea, analysed 62 patients with acute ischaemic stroke receiving fimasartan versus valsartan with the aim of comparing BPV between the two treatment regimens [46]. According to the trial's results, fimasartan showed a greater effect on reducing BPV as measured at 8 weeks compared to valsartan.…”
Section: Blood Pressure Variability Among Patients With Acute Ischaem...mentioning
confidence: 99%
“…One small, single-center, double-blind, randomised clinical trial, that was conducted in Korea, analysed 62 patients with acute ischaemic stroke receiving fimasartan versus valsartan with the aim of comparing BPV between the two treatment regimens [46]. According to the trial's results, fimasartan showed a greater effect on reducing BPV as measured at 8 weeks compared to valsartan.…”
Section: Blood Pressure Variability Among Patients With Acute Ischaem...mentioning
confidence: 99%
“…However, episodes of excessive decrease or increase during the day were not evaluated. The daily dynamics of BP in patients with acute stroke were evaluated using ABPM in several studies [7], including for assessing the effect of antihypertensive drugs [8,9], however, data on the prognostic value of BP in the long term after ischemic stroke (IsI) are limited [10].…”
Section: Introductionmentioning
confidence: 99%